Improvement of Polyhydroxybutyrate Production by Deletion of Csra in Escherichia Coli - Blamey-Alegria, J (Pontificia Universidad Catolica de Valparaiso, 2020)
Background: Poly-3-hydroxybutyrate (PHB) can be efficiently produced in recombinant Escherichia coli by the overexpression of an operon (NphaCAB) encoding PHB synthetase. Strain improvement is considered to be one of critical factors to lower the production cost of PHB in recombinant system. In this study, one of key regulators that affect the cell growth and PHB content was confirmed and analyzed. Result: S17-3, a mutant E. coli strain derived from S17-1, was found to be able to achieve high cell density when expressing NphaCAB with the plasmid pBhya-CAB. Whole genome sequencing of S17-3 revealed genetic alternations on the upstream regions of csrA, encoding a global regulator cross-talking between stress response, catabolite repression and other metabolic activities. Deletion of csrA or expression of mutant csrA resulted in improved cell density and PHB content. Conclusion: The impact of gene deletion of csrA was determined, dysfunction of the regulators improved the cell density of recombinant E. coli and PHB production, however, the detail mechanism needs to be further clarified. How to cite: Wu H, Li S, Ji M, et al. Improvement of polyhydroxybutyrate production by deletion of csrA in Escherichia coli. Electron J Biotechnol 2020;46. https://doi.org/10.1016/j.ejbt.2020.04.005. © 2020